2008
DOI: 10.1016/j.jaut.2008.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of celiac disease and other autoimmune diseases in celiacs and their first-degree relatives

Abstract: The occurrence of other autoimmune diseases in celiac disease families has not been previously reported in a North American population. We investigated the familial aggregation of rheumatoid arthritis (RA), juvenile rheumatoid arthritis/juvenile idiopathic arthritis (JRA/JIA), hypothyroidism, insulin dependent diabetes mellitus (IDDM), and alopecia areata (AA) among individuals in families with celiac disease (CD). Family history information, obtained from questionnaires from the University of California Irvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
1
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(105 citation statements)
references
References 56 publications
6
96
1
2
Order By: Relevance
“…The epidemiology of MAS in autoimmune diseases [28,29,30] remains an open question in many cases. To date, the syndrome has been best studied in sJIAs, with estimates of clinically apparent MAS ranging from 7 to 13% [24,31].…”
Section: Case Definition and Epidemiologymentioning
confidence: 99%
“…The epidemiology of MAS in autoimmune diseases [28,29,30] remains an open question in many cases. To date, the syndrome has been best studied in sJIAs, with estimates of clinically apparent MAS ranging from 7 to 13% [24,31].…”
Section: Case Definition and Epidemiologymentioning
confidence: 99%
“…More than 60% of CD-associated susceptibility loci are shared with at least another autoimmune condition, suggesting common pathogenic mechanisms [7]. Moreover, an increased prevalence of AIDs has been reported among CD cases and their families as well as an increased prevalence of CD in individuals with other AIDs; supporting the ‘autoimmune tautology' [8,9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…1 In children ages 2.5 to 15 years this prevalence has been reported as between 0.3% and 1.3%. [2][3][4] Studies have shown an association between CD and numerous autoimmune and rheumatic conditions including rheumatoid arthritis, 5,6 juvenile idiopathic arthritis (JIA), [7][8][9][10] autoimmune thyroiditis, [10][11][12] autoimmune thrombocytopenic purpura, hemolytic anemia, 6 vasculitis, 5,6 polymyositis and dermatomyositis, 13,14 systemic lupus erythematosus (SLE), 5,6,15,16 scleroderma, 5,6 mixed connective tissue disease, 5 diabetes mellitus, [17][18][19][20][21][22] Sjögren syndrome, 6,10,23,24 and dermatitis herpetiformis. 24 Among the connective tissue disorders, only Sjögren syndrome appears to share the HLA DQ2/DQ8 haplotype with CD.…”
Section: What This Study Addsmentioning
confidence: 99%